2012
DOI: 10.1002/hyp.9421
|View full text |Cite
|
Sign up to set email alerts
|

Tracing sediment sources in a tropical highland catchment of central Mexico by using conventional and alternative fingerprinting methods

Abstract: Land degradation is intense in tropical regions where it causes for instance a decline in soil fertility and reservoir siltation. Two fingerprinting approaches (i.e. the conventional approach based on radionuclide and geochemical concentrations and the alternative diffuse reflectance infrared Fourier transform spectroscopy method) were conducted independently to outline the sources delivering sediment to the river network draining into the Cointzio reservoir, in Mexican tropical highlands. This study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…Recently, studies have demonstrated the promise of spectral reflectance-based (visible and (near) infrared) fingerprinting methods as a quicker and less costly alternative for sediment source apportionment, with considerable potential to expand the temporal resolution of sediment fingerprinting analyses during high-flow events (e.g. Cooper et al, 2014aCooper et al, , 2014bEvrard et al, 2013;Martínez-Carreras et al, 2010;Poulenard et al, 2009;Tiecher et al, 2015).…”
Section: Methodological Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies have demonstrated the promise of spectral reflectance-based (visible and (near) infrared) fingerprinting methods as a quicker and less costly alternative for sediment source apportionment, with considerable potential to expand the temporal resolution of sediment fingerprinting analyses during high-flow events (e.g. Cooper et al, 2014aCooper et al, , 2014bEvrard et al, 2013;Martínez-Carreras et al, 2010;Poulenard et al, 2009;Tiecher et al, 2015).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Belmont et al, 2011;Chen et al, 2016) and during individual events (e.g. Cooper et al, 2014a;Evrard et al, 2013;Poulenard et al, 2012). Therefore, applying sediment fingerprinting on multiple timescales can provide information on possible variations and shifts in the dominant sediment source over short to long term timescales, which can help to better understand the interactions between the factors underlying SS transport.…”
Section: Accounting For Temporal Variabilitymentioning
confidence: 99%
“…More recently, MIR (Poulenard et al, 2009(Poulenard et al, , 2012Evrard et al, 2013) and VIS-NIR (Martínez-Carreras et al, 2010a,b;Legout et al, 2013;Brosinsky et al, 2014a,b;Verheyen et al 2014;Tiecher et al, 2015) spectroscopy has also been applied to trace suspended sediment origin. The prerequisites for use of tracer properties in sediment fingerprinting studies are the conservativeness and the linear additive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Different particle sizes of sediments and potential sources were used in previous sediment fingerprinting studies including <63 μm as the most common size fraction (e.g., Collins et al 2010Collins et al , 2012Devereux et al 2010;Blake et al 2012;Navratil et al 2012;Poulenard et al 2012), <2000 μm (e.g., Minella et al 2004;Fukuyama et al 2010;Evrard et al 2011), <53 μm (e.g., Fox andPapanicolaou 2007), <10 μm (e.g., Caitcheon et al 2012;Smith et al 2012;Olley et al 2013;Wilkinson et al 2013), <250 μm (e.g., Foster et al 2007;Evrard et al 2013). The sources of the different sediment size fractions may vary as a result of different entrainment processes and transport characteristics.…”
Section: Introductionmentioning
confidence: 99%